Exposure to organic vapors in footwear workers - Pérez Olmos, Liliana Margarita; Ardila Barbosa, Wilman Yesid; González Acevedo, Hermes Ramón; Mateus Sánchez, Jairo Enrique; Jaimes Delgado, Pedro Emilio (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The footwear manufacturing process often exposes workers to toxic chemicals, such as Volatile Organic Compounds (VOCs), for long periods of time, occupationally and environmentally, which can cause the appearance of malignant neoplasms in a wide variety of organs and tissues, such as lung cancer (asbestos-induced), bladder (by aniline dyes) and benzene leukemia as referred to by Esquiaqui et al. (2012); Zuluaga et al. (2009) y Partanen et al. (2009), becoming the objective of our study in footwear workers in Bucaramanga, Colombia.